2022
DOI: 10.1155/2022/3384067
|View full text |Cite
|
Sign up to set email alerts
|

Use of Music and Songs as Pedagogical Tools in Teaching English as Foreign Language Contexts

Abstract: The purpose of this research paper is to demonstrate how music can be used in the classroom by describing several methods and providing resources, as well as to demonstrate why music can benefit foreign language learning by reviewing research on the impact of music-related methods on EFL learning and teaching. The researchers relied upon the previous studies and critical and scholarly texts. This study adopts a descriptive study design, which is comprised of a quantitative study in various contexts. The result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 19 publications
1
7
0
1
Order By: Relevance
“…This finding is in line with previous studies that had successfully used songs and games to teach English to primary school students (Ara, 2009;Bhakti et al, 2019;Kumar et al, 2022).…”
Section: Discussionsupporting
confidence: 92%
“…This finding is in line with previous studies that had successfully used songs and games to teach English to primary school students (Ara, 2009;Bhakti et al, 2019;Kumar et al, 2022).…”
Section: Discussionsupporting
confidence: 92%
“…First area was relating to the English aptitude. Using games in teaching English also improved grammar (Lin et al, 2020), writing (Fu et al, 2019;Dashtestani, 2022), pronunciation (Dashtestani, 2022), listening (Dashtestani, 2022;Kumar et al, 2022), speaking (Dashtestani, 2022), problem-solving Ben El Moudden, 2021; Dashtestani, 2022). The second area was delaing with aptitude such as motivation (Dashtestani, 2022;Ahmed et al, 2022), and positive influence (Boyinbode, 2018;Chen et al, 2019;Fithriani, 2021;Kohnke, 2020).…”
Section: Resultsmentioning
confidence: 97%
“…The efficacy of games occurs for some skills of language. Games bring a positive influence on vocabulary (Ben El Moudden, 2021;Dashtestani, 2022;Hao et al, 202;Patra et al, 2022), grammar (Lin et al, 2020), writing (Fu et al, 2019;Dashtestani, 2022), pronunciation (Dashtestani, 2022), listening (Dashtestani, 2022;Kumar et al, 2022), speaking (Dashtestani, 2022), problem-solving Ben El Moudden, 2021Dashtestani, 2022), motivation (Dashtestani, 2022;Ahmed et al, 2022). These findings indicated that games helped learn English.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations